Need Factors Related to Utilization of Oral and Dental Health Services - Yusriani, Yusriani (Universitas Muslim Indonesia, 2023)
Dental and oral problems based on the results of the Basic Health Research (Riskesdas) in 2018 amounted to 57.6% and 10.2% received services from dental medical personnel, so the effective medical demand for dental treatment was very low. There is a high gap between the decreasing visits and the increasing prevalence of dental caries in the last two years at the Dental Polyclinic of Puskesmas Tamalate Makassar. The purpose of this study was to analyze the relationship between need factors and the utilization of health services at the Dental Polyclinic of Puskesmas Tamalate Makassar 2020. This study was an observational analytic study with a quantitative approach with a cross sectional design. The population in this study were 78 patients who visited the dental polyclinic at Tamalate Makassar Public Health Center. Sampling was done by accidental sampling. Data analysis used Chi Square test and linear regression. The results showed that of the 35 respondents who stated negative perceived need, 11.4% did not take advantage of dental and oral health services and. Meanwhile, of the 43 respondents who stated positive perceived need, 37.2% took advantage of dental and oral health services. Of the 31 respondents who stated that the evaluated need did not agree, as many as 100% did not use dental and oral health services. Meanwhile, of the 47 respondents who stated that the evaluated need agreed as much as 100% used dental and oral health services. The results of statistical tests using the chi-square and linear regression test showed that there was a significant relationship perceived and evaluated need factors on the use of dental and oral health services in a positive direction at the Polyclinic of Puskesmas Tamalate Makassar. Conclusion There was a significant relationship between the need factors on the use of dental and oral health services. Puskesmas were expected to be able to maintain and provide good perceptions to patients about their oral and dental health in order to increase the utilization of health services at the dental polyclinic of Puskesmas Tamalate.